The STEPWISE study: study protocol for a smartphone-based exercise solution for people with Parkinson’s Disease (randomized controlled trial) - Sabine Schootemeijer; Nienke M. de Vries; Eric A. Macklin; Kit C.B. Roes; Hilde Joosten; Larsson Omberg; Alberto Ascherio; Michael A. Schwarzschild; Bastiaan R. Bloem (BMC Neurology, 2023)
Abstract Background Exercise has various health benefits for people with Parkinson’s disease (PD). However, implementing exercise into daily life and long-term adherence remain challenging. To increase a sustainable engagement with physical activity of people with PD, interventions that are motivating, accessible, and scalable are needed. We primarily aim to investigate whether a smartphone app (STEPWISE app) can increase physical activity (i.e., step count) in people with PD over one year. Our second aim is to investigate the potential effects of the intervention on physical fitness, and motor- and non-motor function. Our third aim is to explore whether there is a dose-response relationship between volume of physical activity and our secondary endpoints. Methods STEPWISE is a double-blind, randomized controlled trial. We aim to include 452 Dutch people with PD who can walk independently (Hoehn & Yahr stages 1–3) and who do not take more than 7,000 steps per day prior to inclusion. Physical activity levels are measured as step counts on the participant’s own smartphone and scaled as percentage of each participant’s baseline. Participants are randomly assigned to an active control group with an increase of 5–20% (active controls) or any of the three intervention arms with increases of 25–100% (intermediate dose), 50–200% (large dose), or 100–400% (very large dose). The primary endpoint is change in step count as measured by the STEPWISE smartphone app from baseline to 52 weeks. For our primary aim, we will evaluate the between-group difference in average daily step count change from baseline to 52 weeks. For our second aim, measures of physical fitness, and motor- and non-motor function are included. For our third aim, we will associate 52-week changes in step count with 52-week changes in secondary outcomes. Discussion This trial evaluates the potential of a smartphone-based intervention to increase activity levels in people with PD. We envision that motivational apps will increase adherence to physical activity recommendations and could permit conduct of remote clinical trials of exercise for people with PD or those at risk of PD. Trial registration ClinicalTrials.gov; NCT04848077; 19/04/2021. Clinicaltrials.gov/ct2/show/NCT04848077.